Convertible Debt and Earnings per Share: Pragmatism vs. Good Theory. - Frank, Werner G.; Weygandt, Jerry J. (The Accounting Review, 1970)
Abstract The article reports that recently the Accounting Principles Board of the American Institute of Certified Public Accountants issued "Opinion No. 15," on earnings per share, which recommended that a dual presentation of earnings per share should be required and displayed with equal prominence on the face of the income statement. The first earnings per share figure, normally referred to as primary earnings per share, includes not only a weighted average of the common stock outstanding for the year but also considers certain securities to be the equivalent of outstanding common stock and therefore recognizes them in the computation of earnings per share if they have a dilutive effect. These certain securities are classified into four major groupings including convertible debt and convertible preferred stock, stock options, warrants and stock purchase contracts, participating securities and two-class common stocks and contingent shares. While some of the issues developed in this article will apply to all these dilutive instruments, more attention is given to convertible debt.